Where is the market? Assessing the role of dryer performance and marketability of solar-dried products in acceptance of solar dryers amongst smallholder farmers - Korsuk Kumi, Peter G.; Elolu, Samuel; Odongo, Walter; Okello, Collins; Kalule, Stephen W. (Heliyon, 2023)
Agricultural technological development is a crucial strategy for agricultural commercialization and socio-economic transformation in Africa. However, a key challenge to technology use in agriculture remains the limited farmer acceptance of unfamiliar technologies. This paper uses a sample of 245 okra farmers drawn from northern Uganda to assess the drivers of the farmer acceptance of solar drying technology. On the basis of drying performance, farmers perceive the solar dryer to perform better than the open sun-drying method. Structural equation modelling results show that the drying rate and perceived product quality are the main determinants of farmer perceptions on product marketability. Further, product marketability drives acceptance of solar dryers among farmers. We conclude that acceptance of solar dryers is dependent on: i) the drying rate, ii) favorable perceptions towards product quality, and iii) perceived marketability of the solar-dried product. We call for policy action on intensification of efforts that promote solar drying technology, including supporting local artisans to fabricate dryers, to enable increased value addition and consumption of nutritious foods.
Keywords: Technology development; Solar dryer; Renewable energy; Performance; Technology acceptance; Value addition